(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study explored the impact of augmented reality (AR) flashcards on English as a Foreign Language (EFL) learners’ comprehension, retention, and motivation in learning idiomatic expressions. The research aimed to examine how AR technology affects idiom learning outcomes and to explore students’ experiences using AR tool. A mixed-methods approach was employed, combining quantitative data from pre- and post-tests and the Instructional Materials Motivation Survey (IMMS), along with qualitative responses to open-ended questions. The participants were 42 female students at King Abdulaziz University, divided into experimental (AR flashcards) and control (traditional flashcards) groups. Results showed that both traditional and AR flashcards improved idiom comprehension and retention, with no statistically significant difference between the two. However, the AR group demonstrated notably higher motivation levels, particularly in terms of attention, confidence, and relevance, as indicated by IMMS results. Qualitative data further supported these findings, many participants expressing a clear preference for AR flashcards due to their engaging, interactive, and visually supportive nature. The study suggests that while both methods are effective for idiom learning, AR flashcards offer added motivational benefits. It is recommended that future research include a larger and more diverse sample, including male participants, to enhance generalizability.